O ensino do cálculo diferencial e integral na Escola Politécnica de São Paulo, no ano de 1904: uma análise documental - Oliveira, Antonio Sylvio Vieira de [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
O objetivo deste trabalho é analisar o Curso de Cálculo Diferencial e Integral ministrado no curso básico da Escola Politécnica de São Paulo, no ano de 1904. A proposta foi desenvolvida por meio de uma pesquisa histórico-documental realizada nas bibliotecas da Instituição e em outros Centros da Universidade de São Paulo. Inclui uma análise de conteúdo de um texto didático organizado por um aluno da disciplina nesse período, além de outras informações pertinentes sobre o Curso e a Escola. A intenção é investigar a produção de conhecimento e delinear o fazer matemático na Politécnica na época.

The purpose of this project is to analyse the undergraduate course on Differential and Integral Calculus as it was taught in the basic Engineering Course at Escola Politécnica de São Paulo in 1904. The study was developed by means of a historical and documentary research in different libraries and departments of University of São Paulo. The work unfolds the contents of an instructive text compiled by a student regularly enrolled in the mentioned course at the time. Moreover, it also brings about some relevant information and distinctive aspects of the course in question. In brief the project aims at investigating the knowledge production, as well as the learning and teaching procedures at Escola Poltécnica in the first decade of the XXth Century.
Keywords: Matemática - História; Educação Matemática; Mathematics Education